LEGAL PROBLEMS IN THE DRAWING UP OF SALE AND PURCHASE DEEDS OVER LAND STILL HELD AS UNDIVIDED INHERITANCE - Markus Gunawan (Journal of International Islamic Law, Human Right and Public Policy, 2025)
A substantial proportion of certified land in Indonesia remains registered in the name of a deceased rights holder. When the heirs decide to sell before the estate has been partitioned, the Land Deed Official (Pejabat Pembuat Akta Tanah, PPAT) is confronted with a transaction that is economically ordinary but legally precarious. This article examines the legal position of a sale and purchase deed (Akta Jual Beli, AJB) executed over land that is still held as undivided inheritance, and the specific problems that arise in PPAT practice. Using a normative juridical method with statutory, conceptual, and case approaches, the study finds, first, that before partition the heirs hold an undivided collective right, so that an individual heir may in principle dispose of his own abstract share but never of the parcel itself; a deed purporting to transfer the whole object without the participation of all heirs breaches the nemo plus iuris principle and Article 1471 of the Civil Code, and fails the material requirement of the seller's authority to act. Second, it finds that the procedural route prescribed by Article 42 of Government Regulation No. 24 of 1997 and Article 111 of Ministerial Regulation No. 3 of 1997 as amended by Regulation No. 16 of 2021 registration of the inheritance transfer prior to any sale is frequently circumvented, principally to avoid the double tax burden of successive transfers. Third, it identifies eight recurring problem clusters in practice, ranging from concealed heirs and minor heirs to the failure to separate marital property from the estate. The article argues that the PPAT's duty is preventive rather than merely formal, and proposes a verification protocol, harmonisation of the inconsistent paragraphs of Article 111, integration of civil registration data with the land registration system, and fiscal incentives to eliminate dormant estates.